Triphala - An Indigenous Ayurvedic Mouthwash As An Anti-Inflammatory Agent - A Clinical Study - Chatterjee, Shibam; Manohar, Balaji; Shetty, Neema; Mathur, Aditi; Makhijani, Barkha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: An antiplaque agent with minimal side effects that can be used as an effective adjunct to mechanical plaque control is needed. Mouthwash has been used for centuries for medicinal and cosmetic purposes, but in recent years, the rationale behind the use of chemical ingredients has been subjected to scientific research and clinical trials. Herbal medicines are in great demand in the developed as well as in developing countries for primary health care because of their wide biological and medicinal activities, higher safety margin, and lower costs. Triphala mouthwash used in Ayurveda since ancient times, is well-known for its anti-plaque, anti-gingivitis and anti-microbial properties. Aim: To evaluate and compare the effects of an indigenously prepared 0.6% triphala mouthwash on dental plaque and gingival inflammation with a commercially available chlorhexidine mouthwash. Materials and Methods: 20 subjects in the age group of 20-40 years with mild to moderate gingivitis were selected and divided into two equal groups in the study. Following oral prophylaxis, Group I (n=10) subjects were instructed to rinse with 10 ml of 0.2% chlorhexidine mouthwash, Group II (n=10) subjects with 10 ml of 0.6% triphala mouthwash twice daily for 14 days. Oral Hygiene Index-Simplified, Turesky- Gilmore-Glickman modification of Quigley-Hein-Plaque index and Gingival Index were recorded at baseline, 7 and 14 days respectively. Results: Group I and Group II subjects showed statistically significant results in the reduction of the clinical parameters (p < 0.001). Group I subjects showed statistically significant results in reduction of the plaque status (p < 0.05) whereas; Group II subjects showed significant reduction in the gingival inflammation (p < 0.05). Conclusion: Although, 0.2% chlorhexidine mouthwash yielded better results, 0.6%Triphala mouthwash may be used for short duration of time without any potential side-effects as an alternative to chlorhexidine mouthwash in reducing gingival inflammation.